Association between Previous Pelvic Radiation and All-Cause and Cause-Specific Failure of Replacement Artificial Urinary Sphincters. Issue 6 (20th June 2022) - Huang, Mitchell M.; Huffman, Phillip; Dani, Hasan; Knijnik, Pedro G.; da Silva, Arthur F.; Burnett, Arthur L.; Mostwin, Jacek L.; Wright, Edward J.; Cohen, Andrew J.
Abstract : Purpose: In order to accurately characterize how a history of radiation therapy affects the lifespan of replacement artificial urinary sphincters (AUSs), all possible sources of device failure must be considered. We assessed the competing risks of device failure based on radiation history in men with replacement AUSs. Materials and Methods: We identified men who had a replacement AUS in a single institutional, retrospective database. To assess survival from all-cause device failure based on radiation history and other factors, we conducted Kaplan-Meier, Cox proportional-hazards and competing risks analyses. Results: Among 247 men who had a first replacement AUS, men with a history of radiation had shorter time to all-cause device failure (median 1.4 vs 3.5 years for men with radiation vs without radiation history, p=0.02). On multivariable Cox-proportional hazards analysis, previous radiation was associated with increased risk of all-cause device failure (HR: 2.12, 95% CI: 1.30–3.43, p=0.002) . On multivariable cause-specific hazards analysis, prior radiation was associated with a higher risk of erosion/infection (HR: 7.57, 95% CI: 2.27–25.2, p <0.001), but was not associated with risk of urethral atrophy (p=0.5) or mechanical failure (p=0.15). Conclusions: Among men with a replacement AUS, a history of pelvic radiation was associated with shorter time to device failure of any cause. Radiation was also specifically associated with a sevenfold increase in the risk of erosion or infection of replacement AUS, but not with urethral atrophy or mechanical failure. Patients with a replacement AUS should be appropriately counseled on how radiation history may impact outcomes of future revisions.